Informational constraints on interceptive actions of elite football goalkeepers in 1v1 dyads during competitive performance - Shafizadeh, M.; Davids, K.; Correia, V.; Wheat, J.; Hizan, H. (Journal of Sports Sciences, 2016)
The aim of this study was to examine whether perceptual variables can provide informational constraints for the goalkeepers to intercept the ball successfully in 1v1 dyads. Video images of 42 actions (1v1 in direct shots) were selected randomly from different matches and divided into conceded goals (n = 20) and saved actions (n = 22) to investigate interceptive actions of 20 goalkeepers in the English Premier League in season 2013-2014. Time to Contact (TTC) of the closing distance gap between shooter and goalkeeper was obtained by digitising actions in the 18-yard penalty box. Statistical analyses revealed that, in sequences of play resulting in an intercepted shot at goal, goalkeepers closed down outfield players in the X axis, whereas when a goal was conceded, there was a significantly delayed movement by goalkeepers toward the shooters in this plane. The results of canonical correlations showed that a decreasing distance between a shooter and goalkeeper, and accompanied reduction in relative interpersonal velocity followed a temporal pattern. Findings of this study showed how perception of key informational constraints on dyadic system relations, such as TTC, interpersonal distance and relative velocity, constrain elite goalkeepers` interceptive actions, playing an important role in successful performance.